Pelatihan cara cuci tangan yang benar dan penyuluhan cara hidup sehat untuk mencegah terjadinya COVID-19 di SMA Ta’miriyah Surabaya - Indahasari, Noer Kumala; Herliani, Olivia; Purbowati, Rini; Tjandra, Lusiani; Masfufatun, Masfufatun (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2021)
Proper Hand Washing Training and Healthy Living Counseling for The Perevention of COVID-19 at Ta’Miriyah High School Surabaya. The COVID-19 pandemic has not yet been resolved worldwide, nor in Indonesia. Adequate treatment has not been found, so prevention is a rational step that must be maximized. Proper hand washing is one of the health community movements that can suppress the spread of COVID-19. The hand washing training activity at Ta'miriyah High School Surabaya aims to increase students' knowledge about how to wash hands properly to reduce the spread of COVID-19 in society in general, and in the school environment in particular. The result of this training was monitored through the pre-test and post-test scores performed by students before and after the training. The post-test scores were found to be increased compared to the pre-test scores in all classes. Data analysis stated that there was a significant effect of the hand washing training with the increase of students' knowledge about COVID-19 and how to wash hands properly (p<0.05). The conclusion obtained from these results is that the hand washing training can increase students' knowledge about COVID-19 and how to wash hands properly. This result is expected to have a real impact in preventing the spread of COVID-19 in the Ta'miriyah High School Surabaya.